How should we use the Chinese past? Contemporary Confucianism, the 'reorganization of the national heritage' and non-Western histories of thought in a global age. (October 2017) - Jenco, Leigh
In this essay I argue that recent philosophical attempts to 'modernise' Confucianism rehearse problematic relationships to the past that – far from broadening Confucianism's appeal beyond its typical borders – end up narrowing its scope as a source of scholarly knowledge. This is because the very attempt to modernise assumes a rupture with a past in which Confucianism was once alive and relevant, fixing its identity to a static historical place disconnected from the present. I go on to explore alternative means of situating past thought to present inquiry, by examining a debate among early 20th-century Chinese intellectuals over the value of their past heritage in a modern age. Their diverse responses undermine the certainty of a singular or persistent Chinese past, enabling a creative presentism that encourages deliberate filiation with alternative 'tracks' of past practice and thought.